Retrospective detection of Porcine circovirus 3 (PCV‐3) in pig serum samples from Spain. Issue 5 (14th April 2018) - Klaumann, F.; Franzo, G.; Sohrmann, M.; Correa‐Fiz, F.; Drigo, M.; Núñez, J. I.; Sibila, M.; Segalés, J.
Summary: Porcine circovirus 3 (PCV‐3) is an emerging circovirus species that has recently been reported in different countries around the world, suggesting a widespread circulation. In this study, sera samples originating from 654 pigs of different production phases and clinical/pathological conditions, submitted for diagnostic purposes between 1996 and 2017, were randomly selected. Detection of PCV‐3 genome in such samples was attempted with a previously described PCR method, and the partial genome sequence was obtained from selected PCV‐3‐positive samples from different years. Compiled data confirmed that PCV‐3 has been circulating in the Spanish pig population since 1996. The overall frequency of PCV‐3 PCR‐positive samples in the study period was 11.47% (75 of 654). Phylogenetic analysis of twelve PCV‐3 partial sequences obtained showed a high nucleotide identity with the already known PCV‐3 sequences, with minor variations among years. No significant correlation was found between the detection of PCV‐3 and any production phase nor clinical/pathological condition. These results confirm PCV‐3 circulation at least since 1996 in the Spanish pig population with a low/moderate frequency. Although the information obtained was limited, PCV‐3 did not appear to be linked to any specific pathological condition or age group.